Oral hygiene in patients with orthodontic appliances - Stojkovic, Natasa; Petrovic, Dusanka (Education and Research in Health Sciences, 2023)
The therapy with fixed orthodontic appliances in certain circumstances can lead to an increase in the accumulation of dental plaque, the changes in the composition of the oral microorganisms and the difficulties in maintaining oral hygiene. As a result, there is an occurrence of a number of various problems, especially in patients who established poor oral hygiene. The most common problems are gingivitis and the increased frequency of caries. Sometimes the changes on the gingiva can be so pronounced that the time of wearing the appliance must be shortened, and in some cases the therapy has to be stopped. Due to the mentioned problems, good maintenance of oral hygiene in patients using fixed orthodontic appliances is very important. Continuous maintaining of oral hygiene in these patients is considered to be complicated, so they need additional instructions and explanations of what techniques and appliances should be applied when effective removal of dental plaque is considered. It is also necessary, especially for younger patients, to provide constant motivation and support. To maintain oral hygiene, these patients use a number of different tools: standard toothbrushes, and interdental brushes of various sizes and shapes, dental floss and interdental stimulators. Electric brushes and water flossers, whether loaded by pure water or solution, can be used. Antiseptics and fluorides are often used as additional help for oral hygiene. In patients who wear fixed orthodontic appliances, it is necessary to make an effort and use different means to effectively maintain oral hygiene in order for orthodontic therapy to be successful.
Keywords: oral hygiene; orthodontic appliances; dental plaque; teeth brushing; dental floss; fluorides